Impact of Prosthesis-Patient Mismatch on Hemodynamics During Exercise in Patients With Aortic Stenosis After Transcatheter Aortic Valve Implantation With a Balloon-Expandable Valve - Kameshima, Haruka; Izumo, Masaki; Suzuki, Tomomi; Ohara, Hiroshi; Sato, Yukio; Watanabe, Mika; Kuwata, Shingo; Okuyama, Kazuaki; Kamijima, Ryo; Takai, Manabu; Kou, Seisyou; Tanabe, Yasuhiro; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background There is no evidence of hemodynamic performance during exercise in patients with aortic stenosis (AS) after transcatheter aortic valve implantation (TAVI). This study aimed to investigate the changes in kinematic hemodynamics during exercise and determine the impact of prosthesis-patient mismatch (PPM) on the hemodynamics of transcatheter heart valves using exercise stress echocardiography (ESE) in AS patients after TAVI. Methods and Results This study enrolled 77 consecutive patients (mean age 82 ± 5 years, 50.6% male) who underwent ESE 3–6 months after TAVI with a balloon-expandable valve. The effective orifice area index at rest was significantly correlated with the mean pressure gradient (PG) during exercise (p <0.001). The patients were divided into two groups according to the presence of PPM (PPM and non-PPM groups). During exercise, the patients with PPM had a higher left ventricular ejection fraction (74.6 ± 6.1% vs. 69.7 ± 9.6%, p = 0.048), a lower stroke volume index (47.2 ± 14.0 ml/m2 vs. 55.6 ± 14.5 ml/m2, p = 0.037), a significantly higher mean transvalvular PG (21.9 ± 9.1 mmHg vs. 12.2 ± 4.9 mmHg, p = 0.01) and an increased mean PG from rest to exercise (5.7 ± 3.5 mmHg vs. 2.3 ± 2.8 mmHg, p <0.001) compared with patients without PPM. Patients with PPM had a higher pulmonary artery systolic pressure (SPAP) during exercise (57.3 ± 13.8 mmHg vs. 49.7 ± 10.9 mmHg, p = 0.021) and a higher incidence of exercise-induced pulmonary hypertension (43.8 vs. 15.0%, p = 0.037) than patients without PPM. PPM was strongly associated with exercise-induced pulmonary hypertension (hazard ratio: 3.570, p = 0.013). Conclusions AS patients with PPM after TAVI showed a disproportionate increase in the transvalvular PG and SPAP during exercise, and PPM was associated with exercise-induced pulmonary hypertension.